Sintesis Nitroselulosa Dari Serat Rami (Boechmerianivea) Menggunakan Trietilamin - Riza Rizkiah; Kenny Kencanawati; Ahmad Rosidin; Lingga Wibowo (Universitas Insan Cendekia Mandiri, 2021)
Nitrocellulose is cellulose that is titrated into an ester polymer which can be used as a major component in several types of ammunition and explosives and other materials. Hemp (Boehmeria nivea) is a type of fiber plant that is rich in cellulose and thrives in Indonesia. Until now, the need for nitrocellulose in Indonesia is still imported, even though there is a lot of potential for cellulose that can be exploited, one of which is by synthesizing nitrocellulose from the hemp plant. One of the many uses of nitrocellulose derivatives, one of which is propellant. The propellant is the fuel or power source of a rocket engine. Nitrocellulose that can be used for propellants is nitrocellulose with levels between 11-13.3% nitrogen. This study aims to produce nitrocellulose in levels that meet the standards for making propellants. The study was carried out with a cellulose activation procedure using 20% ​​sodium hydroxide and 1 ml of triethylamine per gram of cellulose. Cellulose nitration was carried out using sulfuric acid and nitric acid with the composition of A (1: 1), B (2: 1) and C (3: 1) which were refluxed for 3 hours. Nitrogen determination was carried out using the Kjeldahl method. The results showed that from 3 samples A, B, and C, nitrogen levels were obtained respectively 12.62%, 13.23%, and 12.97%. This shows that the nitrocellulose from the hemp plant (Boehmeria nivea) can be used for propellants. Keywords: Hemp, nitrocellulose, nitration, triethylamine, propellant